18.3k views
3 votes
Which function rule for points would create the translation shown above?

(x, y) + (x+4, y+3)
(x, y) + (x-4, y-3)
(x, y) + (x+10, y+7)
(x, y) + (x-10, y-7)

Which function rule for points would create the translation shown above? (x, y) + (x-example-1
User Addmeaning
by
5.4k points

1 Answer

7 votes

Answer:

Option A

Explanation:

Coordinates of the given points A and A',

A → (-6, -2)

A' → (-2, 1)

Rule for the translation of point A to A',

A(-6, -2) → A'(-6+h, -2+k)

Since, coordinates of A' are (-2, 1)

Therefore, -6 + h = -2

h = 6 - 2 = 4

And (-2 + k) = 1

k = 3

Therefore, rule for the translation will be,

(x, y) → (x + 4, y + 3)

Option A will be the answer.

Which function rule for points would create the translation shown above? (x, y) + (x-example-1
User Marcos Lara
by
5.1k points